Compound crystal form as well as preparation method and application thereof
By preparing compounds with specific crystal forms, the problem of difficulty in controlling the purity of phosphoramidite monomers and the tendency of protective nucleosides to absorb water is solved, achieving the effect of improving the purity and yield of phosphoramidite monomers.
Patent Information
- Application Number
- CN202411309850.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, the purity control of the phosphoramidite monomer is difficult, and the protective nucleoside is mostly amorphous solid powder, which easily absorbs water and affects the purity and yield of the product.
Provided is a compound with a specific crystal form and a preparation method thereof. The compound is mixed with acetonitrile and crystallized at 15-25°C to obtain a crystal form with a specific X-ray powder diffraction pattern.
The crystal type prepared by this method is not easy to deteriorate. It has higher melting points and lower water content and wetness, easy to save, and can improve the purity of the phosphoricide monomer.
Smart Images

Figure CN119350415A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of medical technology, and in particular to a compound crystal form and a preparation method and application thereof. Background Art
[0002] Nucleic acid drugs, as the third largest type of drugs after small molecule drugs and antibody drugs, have become a global focus and hotspot for biopharmaceutical companies. Currently, there are 14 small nucleic acid drugs approved for marketing worldwide. As a key material for the synthesis of nucleic acid drugs, the purity control of phosphoramidite monomers is very important. The supply of nucleoside monomers that meet the quality requirements is a key factor in the commercialization of nucleic acid drugs. The purity requirement of phosphoramidite monomers is generally ≥99.0%, and the difficulty of quality control is even higher than that of general small molecule APIs (Active pharmaceutical ingredients). It takes a long time for companies to accumulate technology to meet the quality control requirements of phosphoramidite monomers. The synthesis route of phosphoramidite monomers usually includes: (1) treating the nucleoside with acyl chloride or anhydride to add a protecting group to the base; (2) then using DMTrCl reagent to add a DMTr protecting group to the 5' to become a protected nucleoside; (3) then using a phosphorus reagent to phosphitylate the phosphoramidite monomer. Among them, the quality of the protective nucleoside directly affects the purity of the phosphoramidite monomer. Moreover, the phosphitylation reaction needs to be carried out in a water-free environment. Water will directly affect the purity and yield of the phosphoramidite monomer product. The existing protective nucleosides are mostly amorphous solid powders, which are very easy to absorb water during storage. Therefore, studying a protective nucleoside that can be stably preserved is of great significance for improving the purity and yield of the phosphoramidite monomer product. Summary of the invention
[0003] The purpose of the present invention is to overcome the above-mentioned technical problems existing in the prior art and to provide a compound crystal form and a preparation method and application thereof.
[0004] In order to achieve the above-mentioned object, the first aspect of the present invention provides a crystalline form of a compound represented by formula (1), wherein the characteristic peaks 2θ of the X-ray powder diffraction pattern of the crystalline form include 4.60°±0.2°, 8.88°±0.2°, 9.74°±0.2°, 10.76°±0.2°, 12.00°±0.2°, 13.54°±0.2°, 16.86°±0.2°, 17.30°±0.2°, 21.08°±0.2°, and 25.36°±0.2°;
[0005]
[0006] The second aspect of the present invention provides a method for preparing the above-mentioned crystal form, which comprises: mixing the compound represented by formula (1) with acetonitrile, adding seed crystals, and then crystallizing at 15-25°C to obtain the crystal form of the compound represented by formula (1).
[0007] The third aspect of the present invention provides the use of the crystalline form of the compound represented by formula (1) described above in improving the purity of phosphoramidite monomers; preferably, the use includes using the compound represented by formula (1) having the crystalline form described above as a raw material for synthesizing phosphoramidite monomers.
[0008] Through the above technical solution, the present invention achieves the following beneficial effects:
[0009] The purity of the nucleoside with a specific crystal form of the present invention changes slightly with the extension of the storage time, which indicates that the crystal form prepared by the method of the present invention is not easy to deteriorate and is easy to preserve.
[0010] The nucleoside with a specific crystal form of the present invention has a higher melting point and lower water content and hygroscopicity. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 This is the XRD pattern of the product prepared in Example 1. DETAILED DESCRIPTION
[0012] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0013] In a first aspect, the present invention provides a crystalline form of a compound represented by formula (1), wherein the characteristic peaks 2θ of the X-ray powder diffraction pattern of the crystalline form include 4.60°±0.2°, 8.88°±0.2°, 9.74°±0.2°, 10.76°±0.2°, 12.00°±0.2°, 13.54°±0.2°, 16.86°±0.2°, 17.30°±0.2°, 21.08°±0.2°, and 25.36°±0.2°;
[0014]
[0015] According to the present invention, preferably, the characteristic peak 2θ of the X-ray powder diffraction pattern of the crystal form also includes 12.62°±0.2°, 14.74°±0.2°, 15.78°±0.2°, 18.02°±0.2°, 18.82°±0.2°, 20.26°±0.2°, 22.94°±0.2°, 23.59°±0.2°, and 24.24°±0.2°.
[0016] According to the present invention, preferably, the structure of the compound represented by formula (1) is
[0017]
[0018] According to the present invention, preferably, the X-ray powder diffraction pattern of the crystal form is as follows Figure 1 shown.
[0019] According to the present invention, preferably, the melting point of the crystalline form is 143-146°C.
[0020] According to the present invention, preferably, the water content in the crystalline form is less than 0.4 wt %. More preferably, the water content in the crystalline form is less than 0.3 wt %. Further preferably, the water content in the crystalline form is less than 0.25 wt %.
[0021] According to the present invention, preferably, the hygroscopicity of the crystal form is less than 101 wt %. More preferably, the hygroscopicity of the crystal form is less than 100.7 wt %. Further preferably, the hygroscopicity of the crystal form is less than 100.4 wt %.
[0022] According to the present invention, preferably, the content of acetonitrile (residual) in the crystalline form is less than 3% by weight, more preferably less than 1% by weight.
[0023] According to the present invention, preferably, the interplanar spacing of the crystal form is 0.3-2nm, and the half-peak width is 0.1-0.7nm. More preferably, the interplanar spacing and half-peak width of the crystal form at different characteristic peaks are shown in Table 1-A,
[0024] Table 1-A
[0025]
[0026]
[0027] In the present invention,
[0028] The second aspect of the present invention provides a method for preparing the above-mentioned crystal form, which comprises: mixing the compound represented by formula (1) with acetonitrile, then adding seed crystals, and then crystallizing at 15-25°C to obtain the crystal form of the compound represented by formula (1).
[0029] In the present invention, when preparing the crystal form of the compound represented by formula (1), seed crystals are added to accelerate the crystallization process, increase the crystallization rate, and form a large number of crystals in a short time; at the same time, the particle size uniformity of the formed crystals can also be improved.
[0030] According to the present invention, preferably, the amount of acetonitrile used is 8-10 mL per gram of the compound represented by formula (1).
[0031] According to the present invention, the conditions for mixing the compound represented by formula (1) with acetonitrile are not particularly limited, as long as the compound represented by formula (1) can be dissolved in acetonitrile. Preferably, the temperature for mixing the compound represented by formula (1) with acetonitrile is 70-80°C.
[0032] According to the present invention, the method further comprises cooling the mixed solution of the compound represented by formula (1) and acetonitrile to 40-50° C. before adding the seed crystals.
[0033] According to the present invention, preferably, the method for preparing the seed crystal is: mixing the compound represented by formula (1) with acetonitrile, heating to 70-80°C to dissolve, placing at room temperature, and standing for 10-16 hours until crystals precipitate, which are the seed crystals. The amount of acetonitrile used is 8-10 mL per gram of the compound represented by formula (1).
[0034] According to the present invention, preferably, the amount of the seed crystal is 0.5-1 g per 100 g of the compound represented by formula (1).
[0035] According to the present invention, preferably, the crystallization is carried out under stirring. The crystallization time can be 10-16 hours.
[0036] According to the present invention, preferably, the method for preparing the compound represented by formula (1) comprises: adding a solution containing dimethoxytriphenylmethane to a solution containing the compound represented by formula (II) to react, thereby obtaining the compound represented by formula (1);
[0037]
[0038] According to the present invention, preferably, the compound represented by formula (II) is
[0039]
[0040] According to the present invention, preferably, the amount of dimethoxytriphenylmethane used is 1-2 mmol per mmol of the compound represented by formula (II).
[0041] According to the present invention, preferably, the temperature of the dripping is 0-5°C; more preferably, the rate of the dripping is 10-50 mL / h.
[0042] According to the present invention, preferably, the solvent in the solution containing dimethoxytriphenylmethane is at least one of pyridine and dimethylformamide; preferably, the concentration of the solution containing dimethoxytriphenylmethane is 0.4-0.8 mol / L.
[0043] According to the present invention, preferably, the solvent in the solution containing the compound represented by formula (II) is at least one of pyridine and dimethylformamide; more preferably, the concentration of the solution containing the compound represented by formula (II) is 0.4-1 mol / L.
[0044] According to the present invention, preferably, the reaction conditions include: temperature of 0-10°C and time of 1-4h.
[0045] According to the present invention, preferably, the method for preparing the compound of formula (1) further comprises: after the reaction is completed, adding a quencher (water) to the reaction system for quenching, then extracting with ethyl acetate to obtain an organic phase containing the compound of formula (II), then washing the organic phase with a lemon water solution (concentration of 10-30% by weight), saturated sodium chloride, and saturated sodium bicarbonate, respectively, and then drying to obtain a crude product of the compound of formula (1). The purity of the compound (crude product) of formula (1) prepared by this method is 75-90%.
[0046] The third aspect of the present invention provides the use of the crystalline form of the compound represented by formula (1) described above in improving the purity of phosphoramidite monomers; preferably, the use includes using the compound represented by formula (1) having the crystalline form described above as a raw material for synthesizing phosphoramidite monomers.
[0047] The synthetic route for preparing phosphoramidite monomers using nucleosides is as follows:
[0048]
[0049] According to the present invention, preferably, the synthesis route of the phosphoramidite monomer using the compound represented by formula (1) in the above-mentioned crystalline form is as follows:
[0050]
[0051] The present invention will be described in detail below by way of examples. In the following examples,
[0052] X-ray diffractometer conditions: the model of the instrument is Ultima IV, the manufacturer is Japan Rigaku Corporation, the voltage is 40 kV, the current is 40 mA, the scanning range (2θ): 3-90°, the step size: 0.02°.
[0053] Preparation Example 1
[0054] This preparation example is used to illustrate the method of synthesizing the compound represented by formula (1) using the compound represented by formula (II). The synthesis route is as follows:
[0055]
[0056] The compound represented by formula (II) is added to the solvent pyridine to obtain a solution containing the compound represented by formula (II) with a concentration of 0.98 mol / L. Dimethoxytriphenylmethane chloride (DMTrCl) is added to pyridine to obtain a solution containing dimethoxytriphenylmethane chloride with a concentration of 0.59 mol / L. Then, at 0-5°C, the solution containing dimethoxytriphenylchloromethane is added dropwise to the solution containing the compound represented by formula (II) at a rate of 30 mL / h. After the addition is completed, the reaction is continued at 0-5°C for 2 hours. When the residual raw material is less than 5% as detected by HPLC, the reaction is stopped. At 0-5°C, water (the volume of water is 5 times the volume of the reaction system) is slowly added to the reaction system for quenching. Then, ethyl acetate (the volume of ethyl acetate is 15 times the volume of the reaction system) is added for extraction and separation. The organic phase is separated and then washed 6 times with a 20 wt% citric acid aqueous solution (the single volume of the citric acid aqueous solution is 5 times the volume of the organic phase) until the TLC spot plate shows that there is substantially no pyridine remaining in the organic phase. Then, saturated sodium chloride aqueous solution, saturated sodium bicarbonate aqueous solution, and saturated sodium chloride aqueous solution are used for washing once each in turn. Then, the crude product containing the compound represented by formula (1) is obtained after drying (drying temperature is 25°C, drying time is 3 hours) and concentration. The amount of dimethoxytriphenylmethane used is 1.4 mmol per mmol of the compound represented by formula (II).
[0057] HPLC analysis showed that the purity of the crude product containing the compound represented by formula (1) was 82%.
[0058] A crude product containing the compound represented by formula (1) 1 H NMR(400MHz,DMSO-d6)δ12.12(s,1H),11.70(s,1H),8.14(s,1H),7.53–7.00(m,9H),6.9 3–6.67(m,4H),6.30(t,J=6.3Hz,1H),5.40(d,J=4.4Hz,1H),4.46(p,J=4.7Hz,1H),4.01( dt,J=6.6,3.7Hz,1H),3.73(d,J=1.5Hz,6H),3.20(ddd,J=31.8,10.4,4.8Hz,2H),2.78( ddt,J=15.3,12.7,6.4Hz,2H),2.39(ddd,J=13.3,8.9,5.4Hz,1H),1.14(d,J=6.8Hz,6H).
[0059] Example 1
[0060] (1) The method for preparing seed crystals of the compound represented by formula (1) is as follows: the crude product containing the compound represented by formula (1) prepared in Preparation Example 1 is mixed with acetonitrile (the amount of acetonitrile used is 8 mL per gram of the compound represented by formula (1)), heated to 80°C to dissolve, and then placed at room temperature. After standing for 10 hours, crystals precipitate, which are the seed crystals.
[0061] (2) The crude product containing the compound of formula (1) obtained in Preparation Example 1 is added to acetonitrile (8 mL of acetonitrile per gram of the compound of formula (1)), and then the temperature is raised to 70°C to completely dissolve the crude product; the temperature is lowered to 40°C, seed crystals are added (0.8 g of the seed crystals per 100 g of the compound of formula (1)), the temperature is further lowered to 25°C, and crystallization is carried out under stirring for 16 hours; the product is then filtered and dried (the drying temperature is 50°C and the drying time is 10 hours) to obtain a white crystalline product. The yield of the product is 95%. The obtained solid product is subjected to X-ray diffraction powder diffraction measurement using Cu-ka rays, and the obtained XRD spectrum is as shown below. Figure 1 As shown, the XRD spectrum data is shown in Table 1-B.
[0062] Table 1-B
[0063]
[0064]
[0065] Example 2
[0066] (1) The method for preparing seed crystals of the compound represented by formula (1) is as follows: the crude product containing the compound represented by formula (1) prepared in Preparation Example 1 is mixed with acetonitrile (the amount of acetonitrile used is 10 mL per gram of the compound represented by formula (1)), heated to 70°C to dissolve, and then placed at room temperature. After standing for 16 hours, crystals precipitated, which are the seed crystals.
[0067] (2) The crude product containing the compound of formula (1) prepared in Preparation Example 1 was added to acetonitrile (the amount of acetonitrile was 10 mL per gram of the compound of formula (1), and then the temperature was raised to 80°C to completely dissolve the crude product; the temperature was lowered to 50°C, seed crystals were added (the amount of the seed crystals was 1 g per 100 g of the compound of formula (1), and the temperature was further lowered to 25°C, and then crystallized under stirring for 12 hours; then filtered and dried (drying temperature was 50°C, and drying time was 10 hours) to obtain a white crystalline product. The yield of the product was 90%. The obtained solid product was subjected to X-ray diffraction powder diffraction measurement using Cu-ka rays, and the data of the XRD spectrum were basically consistent with those in Example 1 and are not shown here.
[0068] Comparative Example 1
[0069] The crude product containing the compound shown in formula (1) obtained in Preparation Example 1 was mixed with methyl tert-butyl ether (MTBE), and then stirred at 25°C for 14h, and a gel-like solid product was obtained by filtration. The gel-like solid product contains residual methyl tert-butyl ether. The product is relatively stable at 40°C, but the residual methyl tert-butyl ether can be removed only when the temperature is raised to a temperature above 45°C. However, at a temperature above 45°C, the compound shown in formula (1) undergoes a DMTr removal reaction and is converted into a raw material. Therefore, it is necessary to dry it under vacuum. The vacuum drying conditions include: a temperature of 40°C, a vacuum degree of ≤-0.08Mpa, and a time of 10h. A white solid was obtained after vacuum drying, and the yield of the product was 80%. Wherein, the amount of methyl tert-butyl ether used was 12mL per gram of the compound shown in formula (1). The obtained solid product was subjected to X-ray diffraction powder diffraction determination using Cu-ka rays. There was no obvious characteristic peak in the XRD spectrum, that is, the solid was an amorphous powder.
[0070] Comparative Example 2
[0071] The crude product containing the compound shown in formula (1) obtained in Preparation Example 1 was mixed with ethyl acetate (EA), heated to 80°C and stirred to dissolve, and then n-hexane was added dropwise to precipitate the product after cooling to 45°C, and a solid product was obtained by filtration. The solid product was dried at a temperature of 45°C, a vacuum degree of ≤0.08Mpa, and a vacuum drying time of 10h. A white solid was obtained after vacuum drying, and the yield of the product was 85%. Wherein, the amount of ethyl acetate used was 5mL and the amount of n-hexane used was 10mL per gram of the compound shown in formula (1). The obtained solid product was subjected to X-ray diffraction powder diffraction determination using Cu-ka rays, and there was no obvious characteristic peak in the XRD spectrum, that is, the solid was an amorphous powder.
[0072] Comparative Example 3
[0073] The method of Comparative Example 2 was followed, except that n-hexane was replaced with an equal volume of n-heptane. X-ray diffraction powder diffraction was measured using Cu-ka rays, and there was no obvious characteristic peak in the XRD spectrum, that is, the obtained product was an amorphous (powder) solid. The yield of the product was 88%.
[0074] Test Case
[0075] The crystals obtained in the above examples and the powder solids obtained in the comparative examples were tested for melting point, water content (KF), hygroscopicity and stability.
[0076] (1) Melting point test method: The melting point was tested using a fully automatic video melting point apparatus (manufacturer: Haineng Future Instrument Technology Group Co., Ltd., model: MP470). The temperature was raised to 90°C at a heating rate of 1°C / min, and then the sample was placed in the fully automatic video melting point apparatus to test the melting point of the sample. The test results are shown in Table 2.
[0077] (2) Water content test method: The water content was tested by Coulometric Karl Fischer titration using an automatic sampler moisture analyzer (manufacturer: Shanghai Hegong Scientific Instrument Co., Ltd., model AKF-CAS6), wherein the furnace temperature was 150° C. The test results are shown in Table 2.
[0078] (3) Hygroscopicity test method: a certain mass of the sample to be tested is placed in an open bottle, and then the open bottle is placed in a constant temperature dryer, which is filled with a saturated ammonium chloride aqueous solution. After being placed at 25±1°C for 24 hours, the weight of the sample after absorbing the moisture in the constant temperature dryer is weighed. The calculation formula for hygroscopicity is: (weight of the sample after absorbing the moisture in the constant temperature dryer - weight of the sample after absorbing the moisture in the constant temperature dryer) ÷ weight of the sample after absorbing the moisture in the constant temperature dryer × 100%. The test results are shown in Table 2.
[0079] (4-1) The sample to be tested was placed under the conditions of 40±2°C and 75±5%RH (relative humidity) for 0 day (T0), 5 days (5D), 10 days (10D), one month (1M), and three months (3M), and then the purity change of the product was tested by high performance liquid chromatography (HPLC). The test results are shown in Table 3.
[0080] (4-2) The samples to be tested were placed under the conditions of 50±5°C and 75±5%RH (relative humidity) for 0 day (T0), 5 days (5D), 10 days (10D), one month (1M), and three months (3M), and then the purity of the products was tested by high performance liquid chromatography (HPLC). The test results are shown in Table 3.
[0081] Table 2
[0082]
[0083] It can be seen from Table 2 that, relative to the comparative example, the crystal form prepared by the method of the present invention has a higher melting point, and lower water content and hygroscopicity.
[0084] Table 3
[0085]
[0086] It can be seen from Table 3 that the crystal form with a specific crystal form prepared by the method of the present invention has a small change in purity as the storage time increases, indicating that the crystal form prepared by the method of the present invention is not easy to deteriorate and is easy to preserve. Compared with the amorphous nucleoside prepared in the comparative example, the nucleoside with a specific crystal form of the present invention is beneficial to improving the purity of the phosphoramidite monomer product.
[0087] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A crystalline form of a compound represented by formula (1), characterized in that: The characteristic peaks 2θ of the X-ray powder diffraction pattern of the crystal form include 4.60°±0.2°, 8.88°±0.2°, 9.74°±0.2°, 10.76°±0.2°, 12.00°±0.2°, 13.54°±0.2°, 16.86°±0.2°, 17.30°±0.2°, 21.08°±0.2°, and 25.36°±0.2°; 2. The crystal form according to claim 1, wherein The characteristic peaks 2θ of the X-ray powder diffraction pattern of the crystal form also include 12.62°±0.2°, 14.74°±0.2°, 15.78°±0.2°, 18.02°±0.2°, 18.82°±0.2°, 20.26°±0.2°, 22.94°±0.2°, 23.59°±0.2°, and 24.24°±0.2°; And / or, the structure of the compound represented by formula (1) is 3. The crystal form according to claim 1, wherein The X-ray powder diffraction pattern of the crystal form is shown in FIG1 .
4. The crystal form according to claim 1, wherein The melting point of the crystalline form is 143-146°C.
5. A method for preparing the crystal form according to any one of claims 1 to 4, characterized in that: The method comprises: mixing the compound represented by formula (1) with acetonitrile, then adding seed crystals, and then performing crystallization at 15-25° C. to obtain the crystal form of the compound represented by formula (1).
6. The method according to claim 5, wherein: The amount of acetonitrile used is 8-10 mL per gram of the compound represented by formula (1); And / or, the preparation method of the seed crystal is: mixing the compound represented by formula (1) with acetonitrile, heating to 70-80°C to dissolve, placing at room temperature, and standing for 10-16 hours until crystals precipitate, which are the seed crystals; and / or, for every 100 g of the compound represented by formula (1), the amount of the seed crystal is 0.5-1 g; And / or, the crystallization is carried out under stirring.
7. The method according to claim 5, wherein: The preparation method of the compound represented by formula (1) comprises: adding a solution containing dimethoxytriphenylmethane to a solution containing the compound represented by formula (II) to react, thereby obtaining the compound represented by formula (1); Preferably, the compound represented by formula (II) is 8. The method according to claim 7, wherein: The amount of dimethoxytriphenylmethane used is 1-2 mmol per mmol of the compound represented by formula (II); And / or, the temperature of the dropping is 0-5°C; And / or, the solvent in the solution containing dimethoxytriphenylmethane is at least one of pyridine and dimethylformamide; preferably, the concentration of the solution containing dimethoxytriphenylmethane is 0.4-0.8 mol / L; And / or, the solvent in the solution containing the compound represented by formula (II) is at least one of pyridine and dimethylformamide; preferably, the concentration of the solution containing the compound represented by formula (II) is 0.4-1 mol / L.
9. The method according to claim 7, wherein: The reaction conditions include: temperature of 0-10°C, time of 1-4h; And / or, the method for preparing the compound represented by formula (1) further comprises: after the reaction is completed, adding a quencher to the reaction system for quenching, then extracting with ethyl acetate to obtain an organic phase containing the compound represented by formula (II), then washing the organic phase with lemon water solution, saturated sodium chloride, and saturated sodium bicarbonate, respectively, and then drying.
10. Use of the crystalline form of the compound represented by formula (1) according to any one of claims 1 to 4 in improving the purity of phosphoramidite monomers; preferably, the use comprises using the compound represented by formula (1) having the crystalline form described in any one of claims 1 to 4 as a raw material for synthesizing phosphoramidite monomers.